Pengembangan Pembelajaran Virtual Reality Berbasis Metaverse Menggunakan Metode ADDIE - Arek Satria; Tata Sutabri (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2025)
The application of Virtual Reality (VR) based on the Metaverse in education is an innovation that can enhance the quality of learning by providing a more interactive and immersive learning experience. This article discusses the development of VR-based learning integrated with the Metaverse using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Through the stages of analysis, design, development, implementation, and evaluation, VR and Metaverse-based learning can be tailored to students' needs, creating a more flexible and collaborative learning experience. The use of this technology allows students to learn independently or in groups, while improving practical skills and creativity. This study shows that by applying the ADDIE model, VR and Metaverse-based learning can be more effective in increasing student motivation and learning outcomes, addressing the challenges of education in the future.